2018
DOI: 10.5937/actaherb1801035p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timing of weed removal and application of pre-emergence herbicides on growth of soybeans

Abstract: Field studies were conducted in 2017 at Concord in northeast Nebraska to evaluate how timing of weed removal and application of pre-emergence (PRE) herbicides influences the growth of soybean. The studies were laid out in a split-plot arrangement of 14 treatments (2 herbicide regimes and 7 weed removal timings) with four replicates. The 2 herbicide regimes were: No PRE and PRE application of a premix of sulfentrazone plus imazethapyr (140 plus 28 g ai ha-1). The 7 weed removal timings were: V1, V3, V6, R2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, with atrazine, a 5% reduction in corn biomass occurred when weeding did not occur until the V4 stage (162 GDD) or until the V5 stage (215 GDD) in 2017 and 2018, respectively; and a further time until weed removal to the V7 growth stage (302 to 323 GDD) occurred with saflufenacil/dimethenamid-P þ pyroxasulfone. A previous study also demonstrated that application of a PRE herbicide substantially delayed the 5% biomass reduction in soybean until the V5 stage compared with the V1 stage without PRE herbicide (Pavlović et al 2018). Any management input that impacts weed interference would likely influence crop growth (as measured by LAI and biomass in this case) with subsequent influence on crop yield; and crop yield is the basis for estimating CTWR (Hall et al 1992).…”
Section: Corn Leaf Area Index and Biomassmentioning
confidence: 82%
See 1 more Smart Citation
“…However, with atrazine, a 5% reduction in corn biomass occurred when weeding did not occur until the V4 stage (162 GDD) or until the V5 stage (215 GDD) in 2017 and 2018, respectively; and a further time until weed removal to the V7 growth stage (302 to 323 GDD) occurred with saflufenacil/dimethenamid-P þ pyroxasulfone. A previous study also demonstrated that application of a PRE herbicide substantially delayed the 5% biomass reduction in soybean until the V5 stage compared with the V1 stage without PRE herbicide (Pavlović et al 2018). Any management input that impacts weed interference would likely influence crop growth (as measured by LAI and biomass in this case) with subsequent influence on crop yield; and crop yield is the basis for estimating CTWR (Hall et al 1992).…”
Section: Corn Leaf Area Index and Biomassmentioning
confidence: 82%
“…The PRE application of saflufenacil/dimethenamid-P þ pyroxasulfone prevented a reduction in LAI even in season-long delayed weed removal (Figure 1). A similar study in soybean indicated that the effect of season-long weed interference on soybean LAI was 38% with PRE application of sulfentrazone þ imazethapyr compared with 71% reduction without PRE herbicide (Pavlović et al 2018). Similar to LAI, corn biomass was greater in 2018 than in 2017.…”
Section: Corn Leaf Area Index and Biomassmentioning
confidence: 92%
“…), koštan (Echinochloa crus-galli L.), vilina kosica (Cuscuta spp. Dodd) i druge (Pavlović et al, 2004;Konstantinović i Meseldžija, 2005a;Vrbničanin i Božić, 2021).…”
Section: Uvodmentioning
confidence: 99%
“…Application of pre.em. herbicides, separately, could not complete protection of soybeans during the longer period from three to four weeks, so there is a need for use of foliar herbicides (alone or in combinations) [39]. Significant differences between the control, the untreated variant, and treated variants in terms of herbicides efficacy were observed (Tables 5 and 6), which indicates the efficacy of the applied combination of herbicides, due to the fact that a larger number of weeds per m 2 was observed on the control plot than on the treated surfaces.…”
Section: First Assessment Second Assessmentmentioning
confidence: 99%